Accuracy of CTSI in Predicting Severity in Acute Pancreatitis Keeping Ranson Score as Gold Standard - Muhammad Junaid Shah, Muhammad Afzal, Mujeeb Alam Khan, Aftab Ullah (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Acute pancreatitis is a common health issue that leads to emotional, physical and financial human burden. Aim: To determine the diagnostic accuracy of CTSI, in predicting the severity of acute pancreatitis, keeping Ranson’s score as Gold Standard. Study design: Cross Sectional study. Methodology: Total of 148 patients were observed by using Sajid’s calculator for sensitivity and specificity, using a sensitivity of 87.5% with a margin of error = 10% and a specificity of 55.3% with a margin of error=10%, with a confidence interval of 95% and a prevalence rate of 20%. Moreover, random consecutive sampling technique was used for sample collection. Data was evaluated by using SPSS version 24. The results were presented as counts (percentage), means and, standard deviation as appropriate. Results: Our study showed that mean age was 42 years with SD±2.25. Twenty eight percent patients were male, 107(72%) patients were female. Diagnostic accuracy of CTSI score keeping Ranson’s score as a gold standard was analyzed as CTSI has the sensitivity 91%, Specificity 59%. Positive predictive value was 81%, Negative predictive value 67%, Diagnostic accuracy was 84%. Practical Implication: The routine use of CTSI has been practiced in our health setup since long but not much research was done to assess the validity of CTSI in our population. Thus present study assessed the effectiveness of CTSI in our population against the local standard validates in our local setup. Conclusion: It was concluded that CT severity index is still a very valuable and relatively inexpensive tool for assessing acute inflammation of pancreas and for predicting the severity of the pancreatitis. Keywords: Diagnostic Accuracy, CTSI, Acute Pancreatitis and Ranson’s Score.